Pluralism and Monotheism: On Apophatic Intolerance - Haw, Christopher A. (Modern theology, 2025)
This paper explores the dangerous yet liberative potentials of so-called monotheistic intolerance, arguing for its importance in pluralistic politics. Drawing upon the work of political theorist Chantal Mouffe, I examine conventional political notions of inclusivity and show how the metaphysics of “the One True God” has political analogs not merely in despotic, exclusive absolutism but in agonistic pluralism. The metaphysical correlate of pluralism, I argue, is not merely in polytheism but in “apophatic intolerance”—the refusal to lay claim upon the Absolute, the denial of its representation—a subtle mechanics at the heart of monotheism. And yet, ambivalently coinciding with this emancipatory intolerance is a violence-laden “Mosaic distinction” between true and false religion. The political theology of Egyptologist Jan Assmann helps us interpret such volatile but crucial intolerance for our own democratic and pluralistic context.